Penerapan Gis (Geographic Information System) Penunjuk Arah Lokasi Sekolah Terdekat Menggunakan Metode Haversine - Muhammad Syahputra Novelan (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
Geographic information system is a location mapping information to find out the distance between one area to another. The system to be designed is implemented with computer software and hardware that is used for data verification, data storage, updating and changing data and analyzing data. The system will be designed to search for the location of the nearest school by applying GIS (Geographic Information System) and utilizing an Android smartphone. So far, this is still done manually by using maps in hard copy form or by asking other people directly. However, information about the location of the nearest school is very ineffective when asked to the nearest community. For this reason, it is necessary to have a system designed to find digital-based school locations. The application is designed using android studio and a database used by mysql to store information about schools. The application to be implemented must use an internet connection so that the GPS (Global Positioning System) can run properly.